2012
DOI: 10.1007/s00464-012-2569-9
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol improves cerebral oxygen content and postoperative recovery after prolonged retroperitoneal laparoscopy

Abstract: After prolonged retroperitoneal laparoscopy, there is an imbalance between oxygen supply and demand. A small dose of mannitol can effectively improve cerebral oxygen metabolism, recovery, and cognitive function after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…[ 13 , 14 ] Intraoperative use of mannitol has been shown to increase the brain oxygen content in patients undergoing long duration retroperitoneal laparoscopic surgery. [ 15 ] Preoperative use of a small dose of mannitol (0.5 mg/kg) is safe and may relieve side effects, such as electrolyte disturbances, hypotension and renal failure. [ 16 ] Based on our results, the fast intravenous drip of a small dose of mannitol increased the urine volume, reduced SCTO 2 , and increased the brain blood flow, further ameliorating the release of inflammatory mediators, such as histamine and 5-HT, and preventing the occurrence of PONV following gynecological laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] Intraoperative use of mannitol has been shown to increase the brain oxygen content in patients undergoing long duration retroperitoneal laparoscopic surgery. [ 15 ] Preoperative use of a small dose of mannitol (0.5 mg/kg) is safe and may relieve side effects, such as electrolyte disturbances, hypotension and renal failure. [ 16 ] Based on our results, the fast intravenous drip of a small dose of mannitol increased the urine volume, reduced SCTO 2 , and increased the brain blood flow, further ameliorating the release of inflammatory mediators, such as histamine and 5-HT, and preventing the occurrence of PONV following gynecological laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol infusion lowers ICP via creating an osmotic gradient between plasma and brain tissue, drawing water from the cerebral extracellular space into the vasculature. 22 Zhou et al 23 suggested the use of mannitol to increase the cerebral oxygen content after prolonged retroperitoneal laparoscopy. However, in their study, cerebral oxygen balance was evaluated through blood gas analysis of samples obtained from the jugular bulb and the radial artery, and mannitol was administered 150 minutes after abdominal insufflation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 20° reverse-Trendelenburg position has been reported to decrease the concentration of cerebral oxy-hemoglobin and total hemoglobin during laparoscopic cholecystectomy [ 4 ]. In addition, such changes in intracranial pressure, cerebral perfusion, and oxygenation lead to longer recovery and impaired cognitive function [ 5 ]. In this study, we hypothesized that there might be a changes in regional cerebral oxygen saturation (rSO 2 ) during laparoscopic gastrectomy and subsequent changes in postoperative cognitive function as compared with conventional open gastrectomy.…”
Section: Introductionmentioning
confidence: 99%